Identifying the Potential of Qur’anic Recitation on the Proliferation of Chondrocytes Derived from Rabbit Articular Cartilage: Work in Progress - Hashim, Rosyafirah; Sha’ban, Munirah; Rahmat, Sarah; Zainuddin, Zainul Ibrahim (IIUM Medical Journal Malaysia, 2018)
Introduction: In Islamic practice, the use of Qur’anic recitation in treatment can be traced back to the times of Prophet Muhammad (PBUH). This preliminary study aims to identify the potential of Qur’anic recitation of Surah Al-Fatihah on the proliferation of chondrocytes derived from rabbit articular cartilage. Cartilage tissue engineering offers an alternative way to facilitate cartilage regeneration in-vitro. Materials and Methods: The cellular model was established using a serially cultured and expanded chondrocytes in-vitro. The model was assigned into three groups. The first group was exposed to the Surah Al-Fatihah, recited 17 times based on the five times daily prayer unit (Raka’ah) obligated upon Muslims. The second group was exposed to an Arabic poem recitation. The third group was not exposed to any sound and served as the control. All groups were subjected to the growth profile analysis. The analysis was conducted at different passages starting from passage 0 to passage 3. Results: The results showed that the cells proliferation based on the growth kinetic analysis is higher for the cells exposed with Qur’anic recitation as compared to the Arabic poem and control groups. Conclusions: The proliferation process of the rabbit articular cartilage might be influenced with the use of Qur’anic recitation and as well as Arabic poem recitation. Exposure to the Western poem recitation and mute sound will be added for future study. It is hoped that this study could shed some light on the potential use of the Qur’anic recitation to facilitate cartilage regeneration in tissue engineering studies.